Kajian Masalah Kesehatan, Tingkat Konsumsi Energi dan Protein, Serta Status Gizi Lansia di Kota Ende - Febronia Melania Woi; Lewi Jutomo; Toy, Sarci Magdalena (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Indonesia is currently experiencing a demographic transition that causes an increase in the population from young to elderly, which has an impact on the health conditions of the elderly. The increase in the elderly raises health issues, especially related to non-communicable diseases, and also the fulfillment of energy and protein nutrients which can affect the nutritional status of the elderly. This study aims to determine health issues, the relationship between energy and protein consumption levels and the nutritional status of the elderly in Mautapaga Village. This type of research is an analytic survey with a cross sectional design, the sampling technique is purposive sampling of 76 people. Energy and protein consumption levels were calculated using the Nutrisurvey program. Analysis of the relationship using the chi-square test. The results showed that the most common health issues of the elderly were non-communicable diseases such as; gout (18.4%), hypertension (14.5%), and cholesterol (13.2%). In addition, there is a significant relationship between the level of energy consumption and the nutritional status of the elderly (p=0.003), but the level of protein consumption (p=0.281) has no relationship with the nutritional status of the elderly. It can be concluded that gout, hypertension, and cholesterol are often experienced by the elderly and the nutritional status of the elderly is more influenced by the level of energy consumption.